2018
DOI: 10.1080/03075079.2018.1445987
|View full text |Cite
|
Sign up to set email alerts
|

What does ‘quality’ in higher education mean? Perceptions of staff, students and employers

Abstract: What does 'quality' in higher education mean? Perceptions of staff, students and employers. 'Quality' in education is difficult to define. What is viewed as high quality by staff, students and employers must be identified so that universities can articulate their offer. Equally, helping students develop the graduate skills and attributes that employers value is essential. This project explored quality in higher education from the perspectives of undergraduate students, academic staff and employers. 340 student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 16 publications
(14 reference statements)
3
71
0
14
Order By: Relevance
“…Students, while being quite positive about teaching and learning methods, expressed uncertainty about the quality of education they receive (Dicker et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Students, while being quite positive about teaching and learning methods, expressed uncertainty about the quality of education they receive (Dicker et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2019) provide the results of an experiment of increasing the accessibility (equality and social justice of applicants and undergraduates) and quality of higher education in China, based on which the scholars substantiate the expedience of increasing the quality for stimulating the development of the digital society and Industry 4.0. Dicker et al (2019) write that the very notion "quality" in higher education could be critically reconsidered in the modern society and economy, as it could be treated differently, depending on the context. For example, in the conditions of Industry 4.0, quality of higher education is based on mastering of digital competencies by students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Staff too, have been identified as important (Thomas, 2015). We previously showed that students rate their relationships with teaching staff as a barometer of a high quality education (Dicker et al, 2017(Dicker et al, , 2018. Relationships with staff and belonging are important components of successful transition into higher education (Thomas, 2015;Carroll-Meehan & Howells, 2018).…”
Section: 'If You Don't Belong It Feels Quite Lonely'mentioning
confidence: 99%